Foodborne disease in Brazil from 2015 to 2021: an exploratory study - OLIVEIRA JUNIOR, Valtemir Paula de; MATTOS, Narlla Nayane de Jesus; AMARO, Lorrayne Ferreira; EGEA, Mariana Buranelo (Food Science and Technology, 2023)
For food to be considered healthy, among other aspects, it must be free of contamination that could lead to the development of foodborne diseases (FBDs). The hygienic and sanitary aspects of food consumed by the population as well as its incorrect handling procedures can cause FBDs. Many contaminated foods seem to have normal sensory characteristics, without changes in texture, flavor, and odor, so often those who consume it do not have the perception and understanding that food that appears to be perfect visibly brings risk internally when consumed, which can cause an FBD. Given these considerations, this study aimed to characterize, report, and quantify the occurrence of outbreaks of FBD affected in the North, Northeast, Midwest, Southeast, and South regions of Brazil between 2015 and 2021 using as a source of data those notified via the Data Sheet Research in the Notifiable Diseases Information System (SINAN). A total of 60,907 cases of food poisoning were recorded across the country due to FBD outbreaks, resulting in 71 fatalities. While the highest number of cases of foodborne outbreaks occurred in the southeast, the highest number of fatalities from FBD occurred in the north of the country. The highest percentage of FBD outbreaks occurred in homes (probably due to the period of the COVID-19 pandemic), although the causative food and the responsible microorganism remained unknown. In this way, it is possible to perceive that in addition to the underreporting that may exist and has already been reported by other articles on the subject, the numbers reported in the Brazilian health system may also demonstrate a lack of investigation into the cause of FBD.